Combined metabolome and transcriptome analyses reveal that growing under Red shade affects secondary metabolite content in Huangjinya green tea - Shu, Zaifa; Ji, Qingyong; He, Tianjun; Zhou, Dayun; Zheng, Shenghong; Zhou, Huijuan; He, Weizhong (Frontiers in Genetics, 2024)
Shading treatments impact the tea (Camellia sinensis L.) quality. The sunlight sensitive varieties can be grown under shading nets for better growth and secondary metabolite content. Here, we studied the responses of a sunlight sensitive green tea variety “Huangjinya” by growing under colored shading nets (red, yellow, blue, and black (75% and 95%) shading rates) to find out the most suitable color of the shading net. Red shading was the most promising treatment as it positively affected the weight and length of 100 one-bud-three leaves and reduced the degree and rate of new shoots burn compared to control (natural sunlight). We then explored the comparative metabolomic changes in response to red shading by using UPLC-ESI-MS/MS system. The amino acids and derivatives, flavonoids, and alkaloids were downaccumulated whereas lipids, organic acids, and lignans were upaccumulated in Red shade grown tea samples. The red shading nets caused a decreased catechin, epicatechin, dopamine, and L-tyramine contents but increased caffeine content. We then employed transcriptome sequencing to find key changes in expressions of related genes and pathways. Notably, key genes associated with the phenylpropanoid and flavonoid biosynthesis pathways exhibited complex regulation. These expression changes suggested a potential trend of polymerization or condensation of simple molecules like catechin or pelargonidin into larger molecules like glucoside or proanthocyanidins. Here, Red shading net triggered higher expression of genes enriched in lipid biosynthesis and jasmonic acid biosynthesis, suggesting an interplay of fatty acids and JA in improving tea performance. These findings contribute to the metabolic responses of Huangjinya tea to red shading nets which might have implications for flavor and health benefits. Our data provide a foundation for further exploration and optimization of cultivation practices for this unique tea variety.